2019
DOI: 10.1007/s10620-019-05929-4
|View full text |Cite
|
Sign up to set email alerts
|

DNAJB6 Promotes Ferroptosis in Esophageal Squamous Cell Carcinoma

Abstract: Background DnaJ/Hsp40 homolog, subfamily B, member 6 (DNAJB6) is significantly down-regulated in esophageal squamous cell carcinoma (ESCC), while its complicated molecular mechanisms are still unknown. Aims To investigate the relationship between DNAJB6 and ESCC. Methods The expression of DNAJB6 was detected in ESCC patient by Western blot and immunohistochemistry. To overexpress DNAJB6a by lentivirus infection, colony-forming, CCK-8, transwell, mouse xenograft assays were utilized to verify the proliferous, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…DNAJB6 is an HSP40 family protein that has significant influence on the inhibition of tumour growth and metastasis. Jiang et al found that DNAJB6 plays an important role in ferroptosis, and its expression is down‐regulated in the oesophageal carcinoma tissues 27 . In addition, the overexpression of DNAJB6 leads to radiosensitization of glioblastoma cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…DNAJB6 is an HSP40 family protein that has significant influence on the inhibition of tumour growth and metastasis. Jiang et al found that DNAJB6 plays an important role in ferroptosis, and its expression is down‐regulated in the oesophageal carcinoma tissues 27 . In addition, the overexpression of DNAJB6 leads to radiosensitization of glioblastoma cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of some genes and proteins can promote ferroptosis in cancer cells. The level of DNAJ/Hsp40 homolog subfamily B member 6 (DNAJB6) is negatively correlated with lymph node metastasis in esophageal squamous cell carcinoma (ESCC) patients, and the overexpression of its isoform DNAJB6a is accompanied by remarkable reduction in the protein levels of GPX4 and phospho-AKT (p-AKT), thus DNAJB6a plays an anti-oncogenic role in ESCC progression via ferroptosis ( 212 ). Signal transducer and activator of transcription-3 (STAT3) can promote ferroptosis through activation of cathepsin B-mediated lysosomal cell death in PANC-1 and CFPAC-1 cells ( 170 ).…”
Section: Ferroptosis and Cancermentioning
confidence: 99%
“…Nrf2 is a core transcription factor that regulates cell oxidative stress, and it exerts an antioxidant/antiapoptotic effect. Multiple studies have shown that AKT and Nrf2 / HO‐1 signaling pathways participate in the regulation of ferroptosis [ 11 , 12 ]. At the same time, the activated AKT and Nrf2 signaling pathways attenuate Erastin‐induced ferroptosis [ 13 , 14 ].…”
mentioning
confidence: 99%